New bidirectional step-up DC-DC converter derived from buck- boost DC-DC converter - Ridha D. N. Aditama; Naqita Ramadhani; Jihad Furqani; Arwindra Rizqiawan; Pekik Argo Dahono (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
This paper proposes a new bidirectional step-up DC-DC converter, namely modified buck-boost DC-DC converter. The proposed DC-DC converter was derived from the conventional buck-boost DC-DC converter. Output voltage expression of the proposed converter was derived by considering the voltage drops across inductors and switching devices. The results have shown that with the same parameter of input LC filter, proposed DC-DC converter has lower conduction losses. Moreover, the proposed DC-DC converter has lower rated voltage of filter capacitor than the conventional boost DC-DC converter which lead to cost efficiency. Finally, a scaled-down prototype of laboratory experiment was used to verify its theoretical analysis.